Sex ratio shift after frozen single blastocyst transfer in relation to blastocyst morphology parameters - Wang, Tiantian; Zhu, Lixia; Yin, Mingru; Yu, Weina; Dong, Jing; Jin, Wei; Lyu, Qifeng; Jin, Lei; Long, Hui (Scientific reports, 2024)
The sex ratio shift was observed in peoples who underwent ART treatment. Moreover, there is limited evidence on differences in sex ratio between single frozen-thawed blastocyst morphology, insemination type and transfer days. So further research is needed in this area with regard to factors possibly affecting the sex ratio. Retrospective study based on multicenter including two large assisted reproduction centers in Shanghai and Wuhan in China. A total of 6361 singleton delivery offspring after frozen-thawed blastocyst transfer. Propensity score weighting and logistic regression models were used to estimate the associations between blastocyst morphology grading and child sex ratio. The main outcome measures is singleton sex ratio. In our study, the primary outcome measure was sex ratio which was calculated as the proportion of male newborns among all live births. Higher quality blastocysts resulted in a higher sex ratio than single poor-quality frozen-thawed blastocyst transfer. Among the three blastocyst morphological parameters of trophectoderm (TE), Grade A and B were significantly associated with a higher sex ratio than Grade C. The similar trend was observed in both IVF and ICSI treated subgroups. As compared with expansion (4 + 3), expansion degree 6 achieved a higher sex ratio in overall populations and IVF treated subgroup. Transferring blastocysts of day 6 had the highest sex ratio both in IVF group and ICSI group. A 6.95% higher sex ratio in transferring blastocysts of day 5 in IVF group than those in ICSI group. No significant association between inner cell mass degree and sex ratio was observed. However, as compared with IVF treatment, all morphology parameters achieved the similar or the biased sex ratio favoring female in ICSI treated subgroup. Quality of blastocysts was positively associated with sex ratio. TE score and expansion degree rather than ICM were significantly associated with sex ratio at birth. ICSI treatment promotes the biased sex ratio favoring female.